2013
DOI: 10.1186/1471-2431-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of exclusive breastfeeding: observations from the Alberta pregnancy outcomes and nutrition (APrON) study

Abstract: BackgroundDespite growing evidence that supports the importance of 6-month exclusive breastfeeding, few Canadian mothers adhere to this, and early weaning onto solids is a common practice. This study assessed infant feeding transitions during the first 6 months postpartum and factors that predicted exclusive breastfeeding to 3 and 6 months.MethodsThis prospective cohort study was part of the Alberta Pregnancy Outcomes and Nutrition study (APrON). From an initial sample of 600 pregnant women recruited from Edmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
68
7
13

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 56 publications
17
68
7
13
Order By: Relevance
“…Interestingly, we found that the paternal role, foods to avoid, body change in mothers, mothers' health and methods to prolong breastfeeding would be important elements for the development of web-based educational information program. These findings agree with those of previous studies on the association between knowledge and attitudes toward breastfeeding [8,9,23].…”
Section: Association Between Optimal Breastfeeding Practice and Totalsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, we found that the paternal role, foods to avoid, body change in mothers, mothers' health and methods to prolong breastfeeding would be important elements for the development of web-based educational information program. These findings agree with those of previous studies on the association between knowledge and attitudes toward breastfeeding [8,9,23].…”
Section: Association Between Optimal Breastfeeding Practice and Totalsupporting
confidence: 83%
“…Also, previous studies have shown that maternal knowledge and attitudes toward breastfeeding may influence the personal decision and intention to breastfeed as well as the duration of breastfeeding [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are numerous breastfeeding promotion campaigns that seek support for mothers and their families from the prenatal period. Direct interventions with the dyads at the beginning of lactation have been shown to be fundamental for a longer duration of this practice (1,8,9) . However, early weaning rates are still alarming in developing countries (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is a natural act; however, breastfeeding may not be simple for some women, because it depends on both the mother-newborn's clinical and anatomical conditions and the meaning that mothers attribute to the breast, body, infant, act breastfeeding and economic, social and cultural circumstances (1,2) . In phonoaudiological terms, breastfeeding facilitates the adequate growth and development of the structures that forms the stomatognathic system and its functions of respiration, suction, swallowing, chewing and speech (3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation